Rough fuzzy approach for web usage mining - Chimphlee, Siriporn; Salim, Naomie; Ngadiman, Mohd Salihin; Chimphlee, Witcha; Srinoy, Surat (WSEAS Press, 2006)
Web usage mining is a new subfield of data mining research. It aims at discovery of trends and regularities in web users' access patterns. In the past few years, web usage mining techniques have grown rapidly together with the explosive growth of the web, both in the research and commercial areas. A challenge in web classification is how to deal with the high dimensionality of the feature space. This paper applies the concept of rough fuzzy approach for classification in web usage mining tasks after we present Independent Component Analysis (ICA) for feature. Clustering is an important part of web mining that involves finding natural groupings of web resources or web users.